Social justice: accessibility to public spaces in contexts of urban exclusion in Ciudad Juárez, Chihuahua, Mexico - Romo Aguilar, Maria de Lourdes; Maldonado, Juan Diego (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Public space goes beyond a territorial unit that is part of the infrastructure since this type of area can contribute significantly and in many ways to the improvement of the quality of life, which is why a fair distribution of this type of space should be equitable and accessible to everyone. That is why the objective of this study is to analyze the accessibility of public spaces in contexts of exclusion from the perspective of social justice in a border city in the north of Mexico, in Ciudad Juárez, Chihuahua. The main tool used in the methodology is spatial analysis, through which public spaces were geo-referenced and categorized to evaluate the accessibility of the population to these sites, and a classification of social exclusion in the city under study was also carried out to later relate the two variables. Among the results obtained, the unequal distribution of access to public areas, their fragmentation and atomization, the lack of equipment and maintenance of these public spaces stand out, and the conclusions are that, although there is apparently a large number of public spaces in Ciudad Juárez, this does not translate into a high indicator of fair access to these spaces and, in fact, the accessibility of the population with high levels of social exclusion is very limited to good quality public places.